Analytical and Clinical Validation for RT-qPCR Detection of SARS-CoV-2 Without RNA Extraction - Miranda, José P.; Osorio, Javiera; Videla, Mauricio; Angel, Gladys; Camponovo, Rossana; Henríquez-Henríquez, Marcela (Frontiers in Medicine, 2020)
Background: The recent COVID-19 pandemic has posed an unprecedented challenge to laboratory diagnosis, based on the amplification of SARS-CoV-2 RNA. With global contagion figures exceeding 4 million persons, the shortage of reagents for RNA extraction represents a bottleneck for testing globally. We present the validation results for an RT-qPCR protocol without prior RNA extraction. Because of its simplicity, this protocol is suitable for widespread application in resource-limited settings. Methods: Optimal direct protocol was selected by comparing RT-qPCR performance under a set of thermal (65º, 70º, and 95º for 5, 10, and 30 minutes) and amplification conditions (3 or 3,5 uL loading volume; 2 commercial RT-qPCR kits with a limit of detection below 10 copies/reaction) in nasopharyngeal swabs stored at 4°C in sterile Weise’s buffer pH 7.2. The selected protocol was evaluated for classification concordance with a standard protocol (automated RNA extraction) in 130 routine samples and 50 historical samples with Cq values near to the clinical decision limit. Results: Optimal selected conditions for direct protocol were: Thermal shock at 70º C for 10 minutes, loading 3.5 ul in the RT-qPCR. Prospective evaluation in 130 routine samples showed a 100% classification concordance with the standard protocol. The evaluation in historical samples, selected because their Cqs were at the clinical decision limit, showed 94% concordance with our confirmatory standard, which includes manual RNA extraction. Conclusions: our results validate the use of this direct RT-qPCR protocol as a safe alternative for SARS CoV-2 diagnosis in case of a shortage of reagents for RNA extraction, with minimal clinical impact.